Estimating NOX, VOC, and CO variability over India’s 1st smart city: Bhubaneswar - Sahu, Saroj Kumar; Mangaraj, Poonam; Tyagi, Bhishma; Yadav, Ravi; Paul, Oscar; Chaulya, Sourav; Pradhan, Chinmay; Das, N.; Sahoo, Pallavi; Beig, Gufran (Frontiers in Environmental Science, 2022)
Volatile organic compounds (VOC) including Benzene, Toluene, Ethyl Benzene, and Xylene (BTEX) in the atmosphere are having severe health and environmental implications. These variables are trace elements in the atmosphere. There are not enough measurement and analysis studies related to atmospheric BTEX variation globally, and the studies are even less in developing countries like India. The present study analyses BTEX variations over an Eastern India site, Bhubaneswar. The continuous measurement of BTEX is first of its kind over Bhubaneswar. The study analyses two years of BTEX data (2017-2018) and attempts to find the relation with meteorological parameters, the significance of ratio between components, along with the analysis of transported air masses. To account the pattern of emissions in association with BTEX variability over the Bhubaneswar, we have also developed emissions details from the transportation sector for the year 2018 and analysed the emission patterns of CO and NOx for the year 2018. The results are indicating that BTEX concentrations are maintained at the site via transportation from other regions, with significant local generation of BTEX, which is smaller in comparison to transported emission.